(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides an overview of the diversity of the animal world of Uzbekistan. The article describes the main species of mammals, birds, reptiles and insects living in various natural landscapes of the country. Particular attention is paid to unique and rare species, as well as their ecological role in the biodiversity of Uzbekistan.